2019
DOI: 10.1128/mcb.00170-19
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 7 Impairs Insulin Signaling and Regulates Aβ Levels through Posttranscriptional Regulation of the Insulin Receptor Substrate 2, Insulin Receptor, Insulin-Degrading Enzyme, and Liver X Receptor Pathway

Abstract: Brain insulin resistance is a key pathological feature contributing to obesity, diabetes, and neurodegenerative disorders, including Alzheimer’s disease (AD). Besides the classic transcriptional mechanism mediated by hormones, posttranscriptional regulation has recently been shown to regulate a number of signaling pathways that could lead to metabolic diseases. Here, we show that microRNA 7 (miR-7), an abundant microRNA in the brain, targets insulin receptor (INSR), insulin receptor substrate 2 (IRS-2), and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 40 publications
(47 reference statements)
1
47
0
Order By: Relevance
“… 30 , 31 In a study miR-7a has been found to impair insulin signaling and regulates extracellular Aβ levels by targeting IRS-2. 32 In our study the bioinformatics analysis by TargetScan suggested that the 3ʹUTR region of IRS-2 gene had a potential binding site for miR-7a, hence we selected miR-7a targeting IRS-2. The outcomes of the present study suggested that expression of miR-7a was significantly inhibited when the expression of IRS-2 was increased in ECs and RPS isolated from DR mice model compared to healthy ones.…”
Section: Discussionmentioning
confidence: 95%
“… 30 , 31 In a study miR-7a has been found to impair insulin signaling and regulates extracellular Aβ levels by targeting IRS-2. 32 In our study the bioinformatics analysis by TargetScan suggested that the 3ʹUTR region of IRS-2 gene had a potential binding site for miR-7a, hence we selected miR-7a targeting IRS-2. The outcomes of the present study suggested that expression of miR-7a was significantly inhibited when the expression of IRS-2 was increased in ECs and RPS isolated from DR mice model compared to healthy ones.…”
Section: Discussionmentioning
confidence: 95%
“…IRS-1 mediates glucose metabolism in AD [ 5 , 138 ], while IRS-2 mediates IR in type 2 diabetes [ 139 ]. However, it has been reported that miR-7 is overexpressed in the cerebellum and frontal cortex of AD patients, reducing the expression of IRS-2, impairing the insulin signaling pathway [ 140 ], and possibly modulating Aβ metabolism during disease progression. It has been reported that miR-126 is involved with micro- and macrovascular complications in type 2 diabetes [ 16 ], and this miRNA was found overexpressed in the cortex and hippocampus in a mouse model of AD [ 132 , 141 ].…”
Section: Mirnas and Ad Pathophysiologymentioning
confidence: 99%
“…Overexpression of miR-7 in AD plays an important role in Aβ metabolism by decreasing IRS-2 expression and suppressing insulin signaling pathway [ 140 ]. Meanwhile, after acute aerobic PE in a cycle ergometer, reduced expression of miR-7 was found in human serum samples [ 231 ].…”
Section: Physical Exercisementioning
confidence: 99%
“…A high miRNA-7 level is associated with high Aβ protein deposits in AD. This miRNA targets Insulin receptor, Insulin Receptor Substrate-2, and Insulin Degrading Enzyme, which are critical to glucose homeostasis and Aβ metabolism in AD ( Fernández-de Frutos et al, 2019 ). In addition, miRNA-7 was found directly correlated with an increase of Aβ protein deposition in neurons and decrease clearance by microglial cells ( Fernández-de Frutos et al, 2019 ).…”
Section: Mirnas As Modulators Of Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%
“…AD patients are often hyperglycemic and have glucose metabolism disorders such as diabetes, leading to a decreased utilization of glucose in affected regions of the brain through disease progression ( Driver, 2014 ). In this regard, miRNA-7 was linked to glucose metabolism in AD where it targets Insulin Receptor Substrate-2 and Insulin Degrading Enzyme ( Fernández-de Frutos et al, 2019 ). Similarly, miRNA-338 contributes to metabolic deregulation as a promoter of glycogen accumulation ( Li C. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%